A comparative study on e-wallet user perceptions: Pre- and post-COVID-19 analysis using e-SERVQUAL - Wahyuni, Nuraida; Fauzan, Zahran; Gunawan, Akbar; Anggraeni, Shanti Kirana; Febianti, Evi; Ekawati, Ratna (Journal Industrial Servicess, 2023)
The use of e-wallets in Indonesia has been developing since their emergence in 2011. The circulation of electronic money has been increasing, particularly in urban areas, due to the rising digital literacy of people. However, there was a significant increase during the Covid period when restrictions were imposed on community activities to prevent the spread of the virus. During this period, the circulation of electronic money more than doubled from the previous year. The perception of e-wallet users is crucial as it provides valuable information about their expectations and preferences. This information helps e-wallet providers determine whether their products or services meet the users' expectations. The e-SERVQUAL method is used to measure e-wallet user perceptions, which evaluates the quality of electronic services provided by companies through electronic media. Therefore, this study aims to investigate whether there is a significant difference in e-wallet user perceptions using e-SERVQUAL before and after the Covid period. The survey method was used in this study. The results showed a significant difference between users' perceptions before and after the Covid period with a significance value below 0.05.